Pengaruh Pemanfaatan Video Pembelajaran Terhadap Hasil Belajar IPA Kelas IV Sekolah Dasar - Prayoga Dwi Jatmiko; Anastasia Wijayatin; Susilaningsih (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
This study aims to determine the effect of the use of instructional videos on the learning outcomes of fourth grade natural science (IPA) subjects at SDN I and SDN III Tasik Honey Trenggalek. The research design used was quasi-experimental (quasi-experimental). This study analyzes whether there are differences in student learning outcomes using instructional video media and not using instructional videos. The results showed that learning using instructional video media was significantly different in the acquisition of learning outcomes compared to learning that did not use instructional video media.